LEGAL BASIS AND PRACTICAL EXPERIENCE OF CRAFTSMANSHIP DEVELOPMENT IN UZBEKISTAN (World Bulletin of Social Sciences, 2025)
The formation of small businesses in Uzbekistan was accompanied by the development of a diversified economy, the transformation of a significant part of it into a form of private property. The reason is that it was impossible to create a truly competitive economic environment in Uzbekistan without fundamentally changing property relations. It was necessary to train craftsmen to work according to world standards. It became an urgent issue to rid the population of Uzbekistan, especially young people, of the spirit of dependency, and to awaken in them a business passion. As a result of measures aimed at developing national crafts in Uzbekistan, in 2016-2021 the number of craftsmen engaged in craft activities increased by 7 times, and the number of apprentices receiving training under their hands increased by 9 times, and the number of people working in it reached 230 thousand people. A national catalog of folk applied arts of craftsmen was created, and 340 masters were included in it. In addition, about 1.5 thousand artisans were included in the tourism register